Beckman Published Information on Software Programs - Eastman, Elke (1985)
The press release discusses Bulletin 7995, a brochure about Beckman Data Capture software.
Keywords: Spectrometer; Marketing; Software; Spectrophotometer; Nuclear counters; Beckman Instruments, Inc.